Teachers and Philosophy: Essays on the Contact Zone, Edited by Cara E. Furman & Tomas de Rezende Rocha, Albany, NY: State University of New York Press, 2025 - Hastangka, Hastangka (Philosophical Inquiry in Education, 2026)
This review critically engages with Teachers and Philosophy: Essays on the Contact Zone, a multi-authored volume that explores the intellectual and pedagogical potential of philosopher-teacher collaborations through the lens of Mary Louise Pratt’s “contact zone.” The review situates the book within ongoing debates in philosophy of education, addressing its response to the decline of philosophical inquiry in teacher preparation and its challenge to the hierarchical separation between academic theorists and educational practitioners. Drawing on diverse methodological and conceptual traditions—including feminist, postcolonial, and dialogic pedagogies—the volume is shown to offer a pluralistic and justice-oriented vision for educational philosophy. Particular attention is given to the international relevance of the work, with chapters addressing Indigenous epistemologies, anti-racist curriculum, and collaborative inquiry across institutional and geopolitical boundaries. While the review acknowledges limitations in the book’s global reach and engagement with digital pedagogy, it concludes that the collection is a significant contribution to contemporary educational thought and a model for philosophizing in and through educational practice.